A rare association of incontinentia pigmenti with congenital heart disease in a newborn - Asha Gowrappala Shanmukhappa; Mounica Chimbili; Leelavathy Budamakuntla; Shilpa Kanathur (Wolters Kluwer Medknow Publications, 2021)
Introduction: Incontinentia pigmenti (IP) is a rare genodermatosis. It classically has manifestations of linear vesicular lesions, evolving into verrucous lesions within few weeks, followed by a peculiar swirled pigmentation lasting for many years. In addition, IP can affect other ectodermal tissues such as the teeth, eyes, bones, and the central nervous system. Case report: We report a case of IP in a newborn female baby who presented to us with verrucous lesions at birth and on examination was found to have congenital heart disease (atrial septal defect, with pulmonary hypertension, tricuspid regurgitation, and predominant right to left shunt). Discussion: We wish to draw attention to the association of IP with congenital heart disease.